2016
DOI: 10.18203/2349-3933.ijam20160194
|View full text |Cite
|
Sign up to set email alerts
|

Serum fibrinogen level in type 2 diabetes mellitus patients

Abstract: Background: Diabetes mellitus is the most common metabolic disorder characterized by metabolic abnormalities and long term complications. The chronic complications of diabetes mellitus affect many organ systems and are responsible for the majority of morbidity and mortality associated with the disease. The aim of the study is to estimate the serum fibrinogen level in patients of Type 2 diabetes and correlate it with parameters like glycemic control (HbA1C), duration of diabetes mellitus, complications and phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
2
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
6
10
2
3
Order By: Relevance
“…Moreover, HbA1c was the stronger predictor of serum fibrinogen than BMI. [15][16][17] In the present study serum fibrinogen did not show significant correlation with age (P-value>0.05). The studies conducted by Jain et al, Bembde, Saini et al and Bruno et al reported that serum fibrinogen had a significant correlation with age.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…Moreover, HbA1c was the stronger predictor of serum fibrinogen than BMI. [15][16][17] In the present study serum fibrinogen did not show significant correlation with age (P-value>0.05). The studies conducted by Jain et al, Bembde, Saini et al and Bruno et al reported that serum fibrinogen had a significant correlation with age.…”
Section: Resultscontrasting
confidence: 63%
“…These findings are similar to other studies. [16][17][18][19][20]23 In the present study correlation between serum fibrinogen was 0.11, 0.20, -0.11, 0.11, 0.59, and 0.45 with TC, LDL cholesterol, HDL cholesterol, TG, HbA1c, and BMI respectively. Jain et al, reported fibrinogen levels were associated with BMI (r = 0.90), TG (r = 0.94), TC (r = 0.99), and HbA1c (r = 0.99) in DM patients in a significant manner.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Similarly Malenica M et al [29] and Agrawal A et al [30] showed positive correlation of IL-6 with FBS and HbA1c. However Dhawale S et al [31] could not document such significant relationship between fibrinogen, FBS and HbA1c. With respect to uric acid, Rabari K et al [32] documented significant linear correlation with both glycemic parameters while Whitehead P et al [33] and Hidayat MF et al [34] could document such relation with HbA1c only.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetes mellitus is the most common metabolic disorder characterized by metabolic abnormalities and long term complications. The chronic complications of diabetes mellitus affect many organ systems and are responsible for the majority of morbidity and mortality associated with the disease [1]. The worldwide prevalence of diabetes mellitus has been increased dramatically over the past two decades and the prevalence of noninsulin dependent diabetes mellitus (NIDDM) is expected to rise more rapidly in future because of increasing obesity and reduced activity levels.…”
Section: Introductionmentioning
confidence: 99%